2009
DOI: 10.1038/sj.bjc.6605147
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Akt sensitises neuroblastoma cells to gold(III) porphyrin 1a, a novel antitumour drug induced apoptosis and growth inhibition

Abstract: BACKGROUND: Gold(III) porphyrin 1a is a new class of anticancer drug, which inhibits cell proliferation of wide range of human cancer cell lines and induces apoptosis in human nasopharyngeal carcinoma cells. However, the underlying signalling mechanism by which gold(III) porphyrin 1a modifies the intracellular apoptosis pathways in tumour cells has not been explained in detail in neuroblastoma cells. METHODS: Cell proliferation and apoptosis were determined by measuring 3-(4,5-dimethylthiazol-2-yl)-2,5-dipheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The importance of free gold porphyrin nanoparticles against neuroblastoma has been shown in previous reports of in vitro and preclinical studies. 23 Consistent with previous findings, our data show that the free gold porphyrin nanoparticles are able to kill neuroblastoma cells. Our in vitro cytotoxicity examination demonstrated the effective killing of neuroblastoma cells using the carrier system.…”
Section: Discussionsupporting
confidence: 93%
“…The importance of free gold porphyrin nanoparticles against neuroblastoma has been shown in previous reports of in vitro and preclinical studies. 23 Consistent with previous findings, our data show that the free gold porphyrin nanoparticles are able to kill neuroblastoma cells. Our in vitro cytotoxicity examination demonstrated the effective killing of neuroblastoma cells using the carrier system.…”
Section: Discussionsupporting
confidence: 93%
“…Further, work was directed to address the possible mechanisms behind therapeutic resistance encountered in neuroblastoma cells. The activation of protein kinase B (PKB), also known as Akt, by ( 18 ) before the onset of apoptosis was postulated as the key reason behind the induction of the encountered resistance [ 69 ]. This hypothesis was strengthened by the fact that the anti-cancer activity of ( 18 ) in neuroblastomas was enhanced after the introduction of Akt/protein kinase B signalling inhibitor (API-2).…”
Section: Gold(i) and Gold(iii) Compounds With Promising Anti-cancementioning
confidence: 99%
“…Among the metal-based compounds used for medical applications, porphyrin gold(III) complexes are receiving increasing attention as chemotherapies rather than PDT drugs because of their promising in vitro and in vivo anticancer activities [ 99 , 100 , 101 , 102 ]. It has been shown that porphyrin is one of the best-stabilizing ligands of gold(III) for avoiding its reduction, and porphyrin substitutions increase its complex solubility and cytotoxicity [ 103 , 104 , 105 ].…”
Section: Gold Porphyrins For the Treatment Of Colorectal Cancermentioning
confidence: 99%